The pattern and the impact of Middle Eastern Tourist spending on Malaysia's economy. - Norlida Hanim Mohd Salleh,; Redzuan Othman,; Mohd Safar Hasim,; Abdul Hamid Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The main objective of this research is to study the spending patterns of tourists from the middle eastern countries and to analyse their impact on Malaysia's economy utilising the input-output method. The Malaysian input output table 2000 is used to estimate the important indicators such as the output, the tax revenue, the import and the employment multipliers. Aside from the data and the information in the input-output table, this study also estimates the expenses of the middle eastern tourists using a survey. The input-output table is aggregated into 18 sectors, and 5 of the sectors are related to tourism. From the estimation the value of the multipliers range 1.109-2.17 for the output multiplier 0.048-0.592 for the import multiplier,0.001-0.194 for the employment multiplier and 0.002-0.053 for the tax revenue multiplier. The differences in the multiplier values would provide a different degree of impact from tourist spending on the sectors in the economy. The sectors that provide more services to tourists would benefit from greater impact than other sectors. The degree of impact experienced by the different sectors is determined by the pattern of tourist spending.